Penerapan Media Blog Dengan Pendekatan Kontekstual Terhadap Keterampilan Menulis Teks Deskripsi Siswa - Muh Irfan; Purnamansyah (Yayasan Pembina Lembaga Pendidikan (YPLP) PGRI Kabupaten Sumbawa Barat - NTB - Indonesia, 2023)
The goal to be achieved in this study is to find out how students write descriptive text skills in the application of blog media with a contextual approach. This study uses research with a quantitative approach with the type of Quasi-Experimental research with Pre-test and Post-test Design. This research was conducted at SMPN 1 Woja. The population in this study were all students at SMPN 1 Woja. The sample selection in this study used a purposive sampling technique with a total sample of 56 students. The instruments used in this study were observation sheets of student activity and descriptive text test questions. Data collection techniques using observation and tests. Data analysis techniques used descriptive statistical analysis and N-Gain which were analyzed using SPSS 29.0 for windows. The results showed that the application of blog media with a contextual approach had an influence on students' ability to write a descriptive text. Analysis of student learning activity data in the experimental class obtained a percentage value of 96.42% while in the control class it was 82.14%. The results of the post-test data analysis showed that the experimental class value was higher than the control class with an average score of 88.57 with an N-Gain value of 0.87 for the experimental class, while in the control class the post-test average value obtained 78.65 with an N-Gain value of 0.62.